. 5. Zapisz wyrażenie, nie używając nawiasów. Zredukuj wyrazy podobne.
a) 2a +(4a - 3b + 5c) + (5c – 2b)
b) 5x + 3y + (2y - 4z) – (5y +6z)
c) -3r - (2r - 4s – t) -(6r + 5s)
d) 4k - (2m + n) - (-k- m) + (3m - n)


Odpowiedź :

Odpowiedź:

a) 2a +(4a - 3b + 5c) + (5c – 2b) =

= 2a + 4a - 3b + 5c + 5c - 2b = 6a - 3b + 10c

b) 5x + 3y + (2y - 4z) – (5y +6z) =

= 5x + 3y + 2y - 4z - 5y - 6z = 5x - 10z

c) -3r - (2r - 4s – t) -(6r + 5s) =

= - 3r - 2r + 4s + t - 6r - 5s = - 11r - 1s + t

d) 4k - (2m + n) - (-k- m) + (3m - n) =

= 4k - 2m - n - k + m + 3m - n = 3k + 2m - 2n

Viz Inne Pytanie